HAK HIDUP ANAK DALAM KANDUNGAN DI LUAR PERKAWINAN YANG SAH DALAM PANDANGAN HAK ASASI MANUSIA - Lucia Charlotta Octovina Tahamata (Faculty of Law, Universitas Pattimura, 2015)
This study to determine examine low the right to be life of unborn children outside of marriage are legitimate. This type of research in the scientific work is normative in this case used statue approach to obtain accurate data respect to the focus of this scientific work. This results showed that right to life of unborn child statue approach. Instrument international universal declaration of human Right year1948 and instrument national Act No 39 year 1999. That the right to life even attached to the baby protect, responsible state in providing protection to children